Towards effective mentoring in general practice. - Freeman, R (1997)
In South Thames, a three-year feasibility study was designed to explore the potential contribution of mentors in furthering professional development and increasing a sense of well-being among general practitioners. The study led to the establishment of an ongoing mentor project as a South Thames (West) Regional initiative, funded by the Postgraduate Dean of General Practice. This paper outlines the project's structure and administration. The concept of the holistic mentor model, together with a strategy (the reflective cycle) for purposeful intervention, is also described. The findings from the evaluation of the study illustrate the response of doctors to their mentor training, their early experience of taking on the role of mentor, and their reporting of the experience of those being mentored (the mentees). The issues relevant to the future of mentoring are commented on, to inform and encourage further discussion.